1994
DOI: 10.23986/afsci.72692
|View full text |Cite
|
Sign up to set email alerts
|

The influence of fertilization and environment on some nutritionally important quality criteria in vegetables - a review of research in the Nordic countries

Abstract: To understand the phenomena caused by nutrient applications on the quality of vegetables, some research has been done in Finland and in Scandinavia during the last decades. Purpose of this review is to evaluate this data against the information available on genetic and environmental factors. Genotype and light intensity highly affect the vitamin C content of plants. Optimal nitrogen level has a small effect, but excess of nitrogen decreases vitamin C content. Genotype, developmental stage of the plant, adequat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 16 publications
1
8
1
Order By: Relevance
“…This is supported also by Simon et al (1982) who showed greater genetic and less environmental variation for sucrose and total sugars. However, the sucrose contents of the present study were slightly lower than reported by Evers (1989b) for the same cultivar.…”
contrasting
confidence: 92%
See 3 more Smart Citations
“…This is supported also by Simon et al (1982) who showed greater genetic and less environmental variation for sucrose and total sugars. However, the sucrose contents of the present study were slightly lower than reported by Evers (1989b) for the same cultivar.…”
contrasting
confidence: 92%
“…ripeness (Fritz and Habben 1974). Also genotype and weather conditions have a clear impact on carrot internal quality (Bradley and Smittle 1965, Simon et al 1982, Miedzobrodzka et al 1993, Evers 1994). Agung and Blair (1989) reported of poor external quality of carrot tap root and decreased fibrous root length density caused by highly compacted soil but, unfortunately, no data on the internal quality were collected.…”
Section: Optimum Soil Compactnessmentioning
confidence: 99%
See 2 more Smart Citations
“…It has previously been shown that salt stress induces an increase in phenolic compounds as a result of the disturbance caused in secondary metabolic pathways 19, 21, 22. Other authors have also described a decrease in phenolics, and mainly in flavonoids, secondary to extended NaCl treatment 8, 23.…”
Section: Resultsmentioning
confidence: 99%